2016
DOI: 10.21726/rsbo.v12i2.744
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of temporomandibular disorder diagnosis: a study on 102 patients undergoing dental treatment

Abstract: Epidemiological studies show that the prevalence of temporomandibular disorders (TMD) is high, ranging from 9.8 to 74%, it is important that the diagnosis be made as early as possible to avoid future clinical failure. Objective: To evaluate the prevalence of TMD in patients attended at the School of Dentistry of Federal University of Juiz de Fora (FO / UFJF), associated with age, gender and clinical group. Material and methods: 102 patients of both sexes were selected during treatment at FO / UFJF in Periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Concerning symptoms, the striking majority complained of clicking (89%) [ 12 ]. In another study, De Oliveira Reis et al reported a similar prevalence of 53.9% in patients present for dental treatment [ 13 ]. Gender differences were significant, with 67.3% female preference and with highest incidence in the age group 41-60 years (52.7%) [ 13 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Concerning symptoms, the striking majority complained of clicking (89%) [ 12 ]. In another study, De Oliveira Reis et al reported a similar prevalence of 53.9% in patients present for dental treatment [ 13 ]. Gender differences were significant, with 67.3% female preference and with highest incidence in the age group 41-60 years (52.7%) [ 13 ].…”
Section: Discussionmentioning
confidence: 95%
“…In another study, De Oliveira Reis et al reported a similar prevalence of 53.9% in patients present for dental treatment [ 13 ]. Gender differences were significant, with 67.3% female preference and with highest incidence in the age group 41-60 years (52.7%) [ 13 ]. Chatzopoulos et al conducted a similar study on a random sample of 4,204 patients present at university dental clinics and retrospectively analyzed data for TMD symptoms.…”
Section: Discussionmentioning
confidence: 95%